Optical Coherence Tomography Reveals New Insights into the Accommodation Mechanism - Mahmoud Mohamed Farouk; Takeshi Naito; Kayo Shinomiya; Hiroshi Eguchi; Khulood Mohammed Sayed; Toshihiko Nagasawa; Takashi Katome; Yoshinori Mitamura (Journal of Ophthalmology)
Purpose. To evaluate the movement of the anterior and posterior lens poles during naturally stimulated accommodation in children using anterior segment optical coherence tomography (OCT). Methods. This is a prospective, observational, noncomparative case series including 18 eyes of nine children. Analysis of the anterior segment in the accommodated and unaccommodated state (with cycloplegia) was done using anterior segment OCT. The main outcome measures were the position of the anterior and posterior lens poles (in relation to the cornea) and lens thickness (LT). Results. A Statistically significant forward movement of the anterior lens pole and backward movement of the posterior lens pole with an increase in LT were found during accommodation (P<0.001). There was no significant difference between the degree of movement of the anterior lens pole and the posterior lens pole during accommodation (P=0.944). Conclusions. Anterior segment OCT provides a rapid noncontact method for studying accommodation in children. The backward movement of the posterior lens pole during accommodation nearly equals the forward movement of its anterior pole. These data minimize the theoretical hydraulic effect of the vitreous during accommodation, adding more support to the capsular theory of Helmholtz.